Transformation from requirement into behavior design: a review - Kamarudin, Nuri Jazuli; Mohd Sani, Nor Fazlida; Atan, Rodziah (IEEE, 2012)
Providing an automated transformation tools to derive UML design diagrams including use cases, activity diagrams from use case requirements is important step of model driven development. This is important because use cases are commonly used for structuring and documenting requirements while activity diagram used to show the flow of the system. However, this step is less preferred by the developer because writing use cases diagram and activity diagram takes time and it must be done manually. Therefore many developers start to develop automation tools from requirement to behavior diagram. The method used in this research are traceability. Traceability will trace the keywords in the requirement to be converted into UML Diagram as proposed. This paper present review on available approaches and tools to support the transformation of requirement into behavior model. The main objective of this paper is to describe and presents the review of the benefits of the existing approach, and the comparison of the tools used in current papers. Finally we will come out with detail discussion and the table shows the differences of the available transformation tools.